Liposome: method of preparation, advantages, evaluation and its application - Pradhan, Bhupendra; Kumar, Narendra; Saha, Suman; Roy, Amit (Creative Pharma Assent, 2015)
Notable research in drug delivery started in 1950’s with the advent of polyclonal antitumor antibodies developed for targeting. Bangham et. Al. discovered liposomes in early 1960’s. In this review article we are discussing about the liposome, methods of the liposome preparation advantages and their different application of the liposome. Liposomes are artificially prepared vesicles made of lipid bilayer. Liposomes can be filled with drugs, and used to deliver drugs for cancer and other diseases. Liposome is used for the targeted drug delivery system and increase the bioavailability and half life of the any drugs. Liposomes are surfactants, sphingolipids, glycol-lipids, long chain fatty acids and even membrane proteins and drug molecules or it is also called vesicular system. Liposomes have been extensively investigated for drug delivery, drug targeting, controlled release and increased solubility.